Connecting the young: High school graduates' matching to first jobs in booms and Great Recessions - Lena Hensvik; Dagmar Müller; Oskar Nordström Skans (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2017)
Using Swedish economy-wide data spanning across two deep recessions, we examine the relationship between labor market conditions and the role of social contacts in matching labor market entrants to employing firms. We use class-plant fixed-effects models to isolate the role of social contacts from paid work during high-school. One third of post-graduation matches are formed at establishments where youths worked during their studies. Furthermore, graduates are much more likely to match with sites to which adult coworkers from these jobs have relocated. These patterns are strikingly counter-cyclical. Contacts are much more important for job matching in deep recessions than in good times, suggesting that informal contacts and social networks are crucial determinants of matching patterns in bad times.
Keywords: J01; 330; job matching; social contacts; business cycle; young workers